PERENCANAAN AREA CHECK-IN PADA BANDARA SULTAN MAHMUD BADARUDDIN II PALEMBANG - Buchari, Erika; Aldy, Fahri (CANTILEVER, 2017)
The increasing number of aircraft passenger has resulted in the density of Sultan Mahmud Badaruddin II Airport. The impact of this density is the long queue in the check-in area that makes the convenience decrease especially in the peak hours. The purpose of this research is to know how the characteristics of passengers and to model the needs of a convenient check-in area for prospective passengers in conducting check-in process. This research method is descriptive, cross tabulation and modeling Multiple Linear Regression.